Students’ perceptions of their preparedness for transition to work after graduation - García-Aracil, Adela (2021)
This study explores the factors that contribute to students’ perceptions of their preparedness for transition from university to work, taking a multidimensional perspective on their academic experience. To that end, a questionnaire was designed and administered to students enrolled in the final year of their master’s degree programme. Students were asked to self-assess their preparedness for the transition to the world of work and also self-assess their academic experience by exploring their academic engagement and the knowledge and competencies they developed during their study. Regarding academic engagement, we find that they consider that participation in lectures and the quality in developing collective work have a positive influence on their preparedness for work, while regular attendance at lectures appears to be negatively associated with their perceptions of their preparedness. The results also show that the practical and theoretical content, together with methodological and employability competencies, have a positive impact on students’ perceptions of their preparedness for transition to work. Thus, the promotion of learning experiences fostering methodological and practical competencies, together with more collective career-related experience and employability skills, may better help prepare graduates for the transition to work.